An exploration of the relationship between burnout, occupational stress and emotional intelligence in the nursing industry - Brand, Tamari (Stellenbosch : University of Stellenbosch, 2007)
Thesis (MA (Industrial Psychology))--University of Stellenbosch, 2007.